Setting social trends in economic system of Ukraine in terms of crisis: legal aspects - Вінник, Оксана Мар'янівна; Кравець, Ірина Мирославівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
In the article, the legal mechanisms setting social trends in economic system of Ukraine are offered in the conditions of crisis. In particular, attention is concentrated on the necessity of the proper control of privatization and post-privatization operation of enterprises; quality of goods and services; pricing; abuse of dominant position in the market to the disadvantage of consumers. The constitutional consolidation (part 4 art. 13) of social trends in Ukrainian economy that should be provided by the state (and the latter according to Art. 1 of the Constitution is social and legal) iscrucially relevant underthe crisis in the economic system of the country during war and considering the substantial loss of the territory (the Autonomous Republic of Crimea, the part of Donetsk and Luhansk regions uncontrolled by Ukraine). Unfortunately, domestic legislation actually contributed to channeling antisocial process of state property privatization,because of legal, semi-legal and illegal distribution of whichthe layer of prominent entrepreneurs was formed alongside the impoverishment of the population. This process is further nurtured by the lack of proper control of: 1) privatization and post-privatization operation of enterprises; 2) quality of goods and services; 3) pricing; 4) abuse of dominant position in the market to the disadvantage of consumers. Privatization process was launched in connection with the transition to a market economic system; its purpose was not only to create a mixed economy, but also socially orientated economy, including socio-economic efficiency of production and attracting funds for the national economy restructuring. This corresponds to enshrinein Art. 13 of the Constitution of Ukraine provisions to ensure the state social orientation of Ukraine's economy. However, in the legislation on privatization the emphasis is made on the transfer of state property into private property, without due control over effective to society (national economy, consumers) use not only for the so-called post-privatization period (with the duty by the new owner to perform contractual obligations) but also after its completion, which is of particular concern in the natural monopolies markets. Social directing economic sphere of the country is provided by the economic systems, whose role in the conditions of economic crisis depends on their level - higher (economy of the country and regions, sectoral economic system) or lower / local (including economic systems with business associations as their centers; holding groups led by holding companies). Local economic systems acting as groups of independent legal entities, interconnected by economic and / or organizational dependence, often ignore the public interests on the grounds of their own survival in the economic crisis. Therefore, in order to protect public interests of society, local communities, consumers it is important for the economic system of the higher level to support consumer interests, as local economic systems often neglect them. As a result, it is advisable to ensure the social character of the economic system of Ukraine in terms of crisis to consolidate appropriate legal mechanisms, in particular, to provide a number of amendments to the legislation (to Laws «On State Property Privatization in regard», «On State Property Fund of Ukraine», «On Protection of Consumers' Rights», «On Protection of Economic Competition», «On Antimonopoly Committee of Ukraine»).